Structure-based design and synthesis of macrocyclic human rhinovirus 3C protease inhibitors. Issue 5 (1st March 2018) - Namoto, Kenji; Sirockin, Finton; Sellner, Holger; Wiesmann, Christian; Villard, Frederic; Moreau, Robert J.; Valeur, Eric; Paulding, Stephanie C.; Schleeger, Simone; Schipp, Kathrin; Loup, Joachim; Andrews, Lori; et al.
Graphical abstract: Abstract: The design and synthesis of macrocyclic inhibitors of human rhinovirus 3C protease is described. A macrocyclic linkage of the P1 and P3 residues, and the subsequent structure-based optimization of the macrocycle conformation and size led to the identification of a potent biochemical inhibitor10 with sub-micromolar antiviral activity.